Physical modeling of stresses during continuous casting of St3S steel - J. Michalik; C. Kolmasiak (Metalurgija, 2009)
In this work the results of physical and numerical modeling of stresses in metal during continuous casting were shown. The numerical research for St3S ingot were realized. Computer program based on Finite Element Method (FEM) was used to simulation. Investigated conditions were based on actual data received from one of polish steel plant. The simulation of continuous casting process was made on GLEEBLE 3800 simulator. The results of thermal load and also stages of bending and straightening of the bloom and stress relaxation phenomenon were shown. Mechanical properties of a solid metal are described by the theory of dislocation that allows taking into account history of changes of stress and strain in the material.